The Relationship between Corporate Governance, Financial Characteristics, Macroeconomic Factors and Performance of Firms Listed at the Nairobi Securities Exchange - Aluoch, Moses Odhiambo; Mwangi, Cyrus Iraya; Kaijage, Erasmus S.; Ogutu, Martin (European Scientific Journal, ESJ, 2020)
This study sought to examine the relationships among corporate governance, financial characteristics, macroeconomic factors and performance of firms listed at the Nairobi Securities Exchange. This study used wealth maximisation theory, agency theory, stewardship theory and stakeholders’ theory to explain the relationships among dependent, intervening, moderating and independent variables. This study employed a census approach and a target population of the study comprised of all companies listed at the Nairobi Securities Exchange from 2002 to 2016. A total of sixty five were used. The data on corporate governance, financial characteristics and performance of firms were extracted from annual reports of the individuals firms and additional data on macroeconomic factors in relation to gross domestic product, interest rates and inflation rates were extracted from Central Bank of Kenya and Kenya National Bureau of Statistics economic reports. This study employed longitudinal descriptive research design to determine relationships amongst variables. A panel data regression analysis was conducted using random effects model which allowed the firms to have a common mean value of the intercept to determine whether corporate governance influence firm performance. The study established that most of the corporate governance practices adopted by listed firms in Kenya had significant effect of the performance of firms. The intervening effect of financial characteristics was determined, while macroeconomic factors were found to have moderating effect in the relationship between corporate governance and performance of listed firms. The study finally established that corporate governance, financial characteristics and macroeconomic factors had a significant joint effect on performance of firms listed on Nairobi Securities Exchange. Based on the findings the study made various conclusions. The study concluded that listed firms in Kenya adopted corporate governance practices as part of the requirements of the regulating authority which had impact on Returns of Assets and Tobin’s Q. The study further concluded that some listed firms in Kenya strengthened their corporate governance due to poor performance; some of the corporate governance practices used by listed firms had negative impact on performance of firms. This study contributed to the existing knowledge since it established that the relationship between corporate governance and firm performance heavily relied on the context under study and for this reason, studies conducted in different context have conflicting results.